A COMPARATIVE ANALYSIS OF HYPOTHESIS IN THE MODELING OF A HYBRID COMPRESSION REFRIGERATION CYCLE - Clemente, A. V.; Lourenço, A. B.; Santos, R. G.; Santos, J. J. C. S. (Revista de Engenharia Térmica, 2024)
This paper presents a comprehensive thermodynamic analysis of a hybrid refrigeration system that integrates an evacuated tube solar thermal collector into a vapor compression refrigeration cycle. The proposed analysis comprises two distinct approaches: an isovolumetric model and a compressible flow model. The former assumes a constant specific volume within the solar heat exchanger, while the latter applies principles of compressible fluid dynamics. The study compares these models with a reference work, emphasizing similarities and disparities. The investigation systematically varies key parameters, including evaporator and condenser temperatures, inlet and outlet temperatures of the heat exchanger, and heat load. By varying these parameters, the coefficient of performance (COP) and compressor work are evaluated, elucidating the impact of heat addition on the system’s performance. Additionally, the influence of different working refrigerant fluids, such as R22 and R410A, is examined under various design point conditions. The results demonstrate the potential energy savings achievable by the hybrid system, with reductions in electrical power compared to the conventional compressor, as solar heat is introduced. While the isovolumetric analysis closely aligns with the reference work, the compressible flow modeling highlights sensitivity to inlet conditions. Although not directly comparable, the latter approach presents promising trends within specific design point ranges. Comparisons of performance curves for different refrigerant fluids further validate the models and assist in potential fluid selection. Overall, the outcomes indicate a promising avenue for energy-efficient refrigeration systems and provide valuable insights for engineering design and optimization.